Modifying the request behaviour of clinicians. Issue 3 (March 1992) - Gama, R; Nightingale, P G; Broughton, P M; Peters, M; Ratcliffe, J G; Bradby, G V; Berg, J
Abstract : Aim: To evaluate whether the feedback of laboratory use and cost data to clinicians modifies their request behaviour. METHODS: Over two years the effect of monthly feedback of clinical chemistry test use and revenue expenditure to three consultant physicians on their clinical chemistry and haematology requesting patterns was evaluated. Two physicians who received no information served as controls. RESULTS: Feedback over one year led to an immediate and sustained decrease of 15%, 27%, and 21% in clinical chemistry requests (p less than 0.01), tests (p less than 0.001), and revenue expenditure (p less than 0.001), respectively, and a 10% reduction in haematology tests (p less than 0.05) per outpatient visit. These changes persisted in the six months after the feedback was stopped. CONCLUSIONS: These results suggest that feedback of laboratory data to clinicians modifies their request behaviour and that supplying clinicians with information on what they do can influence the way they make decisions.